Employment of people with Down syndrome: A scoping review - Ting, Chuong H.; Rahman, Md M.; Chen, Yoke Y.; Safii, Razitasham; Puteh, Sharifa EW.; Saimon, Rosalia; Adenan, Abg S. (Narra Sains Indonesia, 2024)
Down syndrome is the most prevalent genetic condition contributing to intellectual disability. Advancements in medical care have significantly increased the life expectancy of people with this condition, making employment a vital component for independent living and quality of life. The aim of this study was to examine the current literature on the employability and employment experiences of individuals with Down syndrome, focusing on the evolution of the employment rate and factors influencing employment such as cognitive and personal factors, societal attitudes, challenges, and effective support systems. Using Arksey and O’Malley's methodology, a scoping review of relevant qualitative and quantitative articles from PubMed, Scopus, Web of Science (WoS), CINAHL, and Medline was conducted. The search focused on the keywords found in the title and abstract of articles from 1980 to 2023. The search strategy utilized medical subject headings (MeSH), including